ANALISIS KOMPARASI PENDAPATAN USAHATANI PENGOLAHAN KOPI DAN PENDAPATAN USAHA LAINNYA DI DESA KAONGKEONGKEA KECAMATAN PASARWAJO KABUPATEN BUTON - Safrin Edy (Media Agribisnis, 2019)
The purpose of this study was to analyze the income of coffee farms and other businesses and analyze the relationship of income with quality of life. The variables observed were the characteristics of respondents which included: age, the experience of farming, area of ​​arable land, family dependents, education and quality of life, namely income. The study was conducted in Kaongkeongkea Village, Pasarwajo Sub-district, Buton Regency, from March to April 2018. The selection of locations in this study was determined intentionally, based on considerations as a coffee-producing area and coffee processing (agro-industry). The sample in this study amounted to 51 heads of households who were determined by a simple random sampling method. The analysis used was descriptive analysis with a Likert scale method. The results showed that the level of income from the coffee agro-industry business was highly determined by the results of the production of coffee obtained once a year, so the results were lower than other businesses. Furthermore, the relationship between the two variables was shown by the amount of contingency coefficient that is equal to 0.577 with a significant value of 0,000. This means that the level of quality of life is closely related to the income of farmers. It also indicates that the higher the income of coffee agro-industries and other businesses, the better the quality of life of coffee farmers. Keywords: Coffee Agro-Industry Income, Other Businesses, Quality of Life